Financial leverage and ASEAN corporate governance scorecard on accounting conservatism - Diyah Santi Hariyani; Afrida Dwi Agustine; Wenni Wahyuandari; Eni Minarni (Jurnal Ekonomi Modernisasi, 2022)
This study aims to examine the effect of financial leverage and the ASEAN Corporate Governance Scorecard (ACGS) on accounting conservatism.  This study uses a quantitative descriptive research approach to test hypotheses. The population includes companies that are on the Kompas 100 stock index. The sampling method used is purposive sampling, which is a company that is in the top rank 50 of the ASEAN Corporate Governance Scorecard for the period 2017-20 20. After the data was selected, there were 40 companies selected according to predetermined criteria. The analysis method uses multiple linear regression with SPSS 23. The results of this study show that Financial Leverage has a significant effect on Accounting Conservatism and the ASEAN Corporate Governance Scorecard has a significant effect on Accounting Conservatism. The results of this study are in line with the phenomenon in Indonesia that 40 companies that have been included in the ASEAN Top 50 were awarded the ACGS, this shows that corporate governance in Indonesia is still weak. The results of this study do not support the agency theory and the theory of the firm. The results of this study can be used by the OJK in improving the standards of good corporate governance.